Creating a Digital Insurance Model: A Grounded Theory Approach - Mohammad Adabi; Nastaran Haji Heydari; Hamed Vares (‫مدیریت بازرگانی)
Objective Digital transformation can impact companies, business models, communications, and products, enhancing company performance and driving growth. The primary objective of this research is to develop a conceptual model for digital insurance.